The History of Don Quixote, Volume 2, Part 25 - Cervantes Saavedra, Miguel de, 1547-1616; Doré, Gustave, 1832-1883; Ormsby, John, 1829-1895 (Salt Lake City, UT : Project Gutenberg, 2004)
"The History of Don Quixote, Volume 2, Part 25" by Miguel de Cervantes Saavedra is part of a novel originally published in two parts in 1605 and 1615. The story follows Alonso Quijano, a hidalgo who loses his sanity from reading chivalric romances and becomes the knight-errant Don Quixote. Joined by his earthy squire Sancho Panza, he embarks on adventures where fantasy collides with reality. This groundbreaking work explores the tension between illusion and truth as master and servant influence each other's worldviews. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Don_Quixote
Release date is 2004-07-23
Produced by David Widger
Keywords: Spain -- Social life and customs -- 16th century -- Fiction; Knights and knighthood -- Spain -- Fiction; Picaresque literature; Romances